2022
DOI: 10.18502/kss.v7i1.10210
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Inflexibility Moderates Stress and Loneliness in Depression Among Indonesian College Students During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has had a tremendous impact on college students’ mental health. Recent studies have found increased perceived stress and loneliness during the pandemic, which are significant risk factors for depression. However, few researchers have specifically discussed the particular factors that can exacerbate the impact of these risk factors on depression. Psychological inflexibility is said to have an important role in facilitating the development of mental health problems. The current study explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Total scores range from 7 to 49, with higher scores indicating higher PI. The Indonesian AAQ-II has been well-validated using a (Radyani et al, 2022). This study also indicated good internal consistency (Cronbach α=0.904).…”
Section: Measurementsmentioning
confidence: 61%
“…Total scores range from 7 to 49, with higher scores indicating higher PI. The Indonesian AAQ-II has been well-validated using a (Radyani et al, 2022). This study also indicated good internal consistency (Cronbach α=0.904).…”
Section: Measurementsmentioning
confidence: 61%
“…Measurement of psychological inflexibility using the Acceptance and Action Questionnaire (AAQ-II) developed by Bond, Hayes, et al (2011) and has been translated into Indonesian by Radyani, Indra, & Oriza (2022). AAQ-II consists of seven statements and each statement consists of seven answer choices, namely "Never happens", "Very rare", "Rare", "Happens sometimes", "Happens often", "Almost always happens".…”
Section: Methodsmentioning
confidence: 99%